Transcriptional control of dendritic cell development and functions - Amon, Lukas; Lehmann, Christian; Baranska, Anna; Schoen, Janina; Heger, Lukas; Dudziak, Diana (Immunobiology of Dendritic Cells Part B, 2019)
Dendritic cells (DCs) are major regulators of adaptive immunity, as they are not only capable to induce efficient immune responses, but are also crucial to maintain peripheral tolerance and thereby inhibit autoimmune reactions. DCs bridge the innate and the adaptive immune system by presenting peptides of self and foreign antigens as peptide MHC complexes to T cells. These properties render DCs as interesting target cells for immunomodulatory therapies in cancer, but also autoimmune diseases. Several subsets of DCs with special properties and functions have been described. Recent achievements in understanding transcriptional programs on single cell level, together with the generation of new murine models targeting specific DC subsets, advanced our current understanding of DC development and function. Thus, DCs arise from precursor cells in the bone marrow with distinct progenitor cell populations splitting the monocyte populations and macrophage populations from the DC lineage, which upon lineage commitment can be separated into conventional cDC1, cDC2, and plasmacytoid DCs (pDCs). The DC populations harbor intrinsic programs enabling them to react for specific pathogens in dependency on the DC subset, and thereby orchestrate T cell immune responses. Similarities, but also varieties, between human and murine DC subpopulations are challenging, and will require further investigation of human specimens under consideration of the influence of the tissue micromilieu and DC subset localization in the future.
CRIS-Team Scopus Importer:2019-11-29
Keywords: Antigen presentation; BatF3; CDP; Cross-presentation; DC; Dendritic cell; IRF; Lineage commitment; Ontogeny; Progenitor; Transcription factor; Zbtb46